Sistem Informasi Absensi Berbasis Web pada ASN dan non-ASN di SMP Negeri 1 Tinggimoncong Kabupaten Gowa Menggunakan Metode PIECES - Farid Aidil Fitrah; Faisal Akib; Erfina Erfina (Jurnal ilmiah Sistem Informasi dan Ilmu Komputer, 2025)
Attendance is crucial for any institution or business. Attendance is crucial because it affects the performance of employees or staff in a company. Therefore, its implementation requires accuracy and precision to avoid hindering employees' work. The research method used in this web-based attendance system for civil servants (ASN) and non-ASN (Non-ASN) at SMP Negeri 1 Tinggimoncong is descriptive. The development of systems analysis, design, development, implementation, and maintenance are expected to assist the system. The system was developed using Visual Studio Code with a SQL Server 8000 database. This web-based attendance system application will record data and attendance for civil servants (ASN) and non-ASN within the school, including arrival and dismissal times, in a systemized and computerized website. As an added advantage, this thesis integrates a live camera feature and factual location verification during the attendance process. This ensures that the attendance process is actually carried out by the relevant person in real time and at the designated location, thereby minimizing the potential for manipulation of attendance data. This feature makes the attendance system more accurate, secure, and transparent, and can be trusted as a digital tool for evaluating employee discipline.